IDENTIFIKASI AIR LAUT TERHADAP AIR TANAH MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DI KELURAHAN MUNDAM KOTA DUMAI - Mei Saroh; Usman Malik (Universitas Riau, 2023)
Seawater intrusion has a serious impact on the availability of clean water for the population. Indications of seawater intrusion in several locations in Mundam Village, Dumai City are shown by fluctuations in resident well water from fresh water to brackish water to salt water. This study aims to determine the seawater intrusion zone that occurs using the geoelectric method of the Schlumberger configuration in Mundam Village, Dumai City and to determine the water quality around the research area using several parameters, namely pH, salinity, total dissolved solid, and Turbidity. 1D data processing is carried out with progress software and a 1D cross-sectional model is obtained. This research was conducted on 2 tracks with a distance of 100 meters for each track. The results of the inversion using progress software can be seen that seawater intrusion occurs on line 1, the resistivity value is 0.46 Ωm with a depth of 14.74 – 22 m. Line 2 no longer contains seawater because the distance is more than 1 km from the coast. The depth of groundwater on track 2 is 15.09 – 22 m with a resistivity value of 1.59 Ωm so that at a distance of more than 1 km from the coast it is very good for residents to use drilled wells to get water suitable for consumption.